Town Crier and Rural Information Dissemination in Nigeria: The Bayelsa State Experience - Etebu , Abraham Tabor; Okokuro, Aderonke (MiddleBelt Journal of Library and Information Science, 2015)
Information for sustainable development is seen as a resource and ingredient in the developmental process in rural Africa. Bayelsa State of Nigeria is predominantly rural and mostly of an illiterate populace. Much needed information can only be meaningful to the people if it is well packaged and disseminated in the way and manner they are used to. The role of the town crier in disseminating information in the manner consonant with the rural dwellers’ understanding has been recognized as the major medium through which Government can reach the people adequately. With the use of information and communication technology (ICT), town criers are now able to reach their targeted audience from a central point (radio house), instead of pounding the bits to cover the entire community as in the past. The paper highlighted the role of the town crier; qualities of the town crier; activities of the town crier; the Bayelsa State situation; State Government’s use of town criers; and concluded that town crying as a major means of information provision and dissemination is still very relevant in this modern information age in the 21st century. The paper finally recommended among others that Town Criers should be gainfully employed in the civil service and Librarians in the public libraries serve as intermediary and partner the Town Criers.